PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP MOTIVASI DAN KINERJA KARYAWAN PT ANGKASA PURA II CABANG BANDARA SULTAN SYARIF KASIM II PEKANBARU - Fansuri Ario; Zulfadil Zulfadil; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims determine the influence of leadership and organizational cultureto motivation and employee perfomance of pt. angkasa pura II (persero) kantor cabangbandara sultan syarif kasim II pekanbaru. Populations in the study to 263 peoples andsampling technique is using slovin method. So the sample amounts to 159 peoples. Thedatas is testing by instumental testing whit is the validity test, reability test and classicassumption test. The analytical methods of this research is using descriptive analysis andpath analysis using SPSS 23 for windows. The result of this study showing that thevariables leadership and work dicipline had significant effect on work motivation andemployee perfomance and work motivation had significant on employee perfomance. Thisstudy also showed that variables leadership and organizational culture had significanteffect on employee perfomance with work motivation as intervening variable. Thecoefficient of determination (R2) structure I is equal to 0.646 with showing the variableleadership and work dicipline had influencing on work motivation about 64.6%. Thecoefficient of determination (R2) structure II is equal to 0,709 with showing the variableleadership, work dicipline and work motivation had influencing on employee perfomanceabout 70,9%.Keywords : Work Motivation, Employee Perfomance, Leadership, OrganizationalCulture